Policy preferences of experts seeking to raise and stabilise farm incomes in the Eastern Gangetic Plains - Cooper, Bethany; Crase, Lin; Burton, Michael; Rigby, Dan; Alam, Mohammad Jahangir; Kishore, Avinash (Wiley, 2023)
Poverty is endemic in the highly populated Eastern Gangetic Plains where agriculture is critical to more than half the population. However, the mechanisms to support agriculture for development are contested. For example, some have advocated a strong role for government support and assistance due to market weaknesses, while others have promoted the need for more market-oriented approaches. We use an elicitation process focussed on expert policymaking communities, employing stated preference techniques to explore these options. Differences in perceptions about the effectiveness of policies and their delivery are reported between countries, while also empirically examining the influence of the respondents' organisational background. The results show support for policies that improve farmers' access to inputs, especially when delivered by private sector actors. The research provides an important contribution to the literature on policies for agricultural development.